The Effect of Microcirculation Disturbance of Peribiliary Vascular Plexus on Hepatic Bile Duct Epithelial Cells in Rats Undergoing Liver Transplantation and Postoperative Rejection Reduction by Nanocarrier Mediation: Liver Transplantation and Postoperative Rejection Reduction by Nanocarrier - Yuan, Zhigao; Zhou, Mai; Deng, Wuyi; Wang, Daqing; Jiao, Gangjun (Cellular and Molecular Biology, 2022)
This study was to investigate the effect of microcirculation disturbance of PVP on HBD epithelial cells in rats undergoing liver transplantation and to explore the postoperative rejection reduction by nanocarriers mediation. For this aim, adult male rats weighing 210–250 g, were fed cleanly and were subjected to liver transplantation. 3 days after the surgery, the rats were randomly divided into three groups based on different intervention factors: group A (HAL), group B (HAMI combined with HAL), and group C (control). The three groups of rats were divided into three subgroups according to the duration of the University of Wisconsin (UW) solution (UW time) used to preserve the donor organs for transplantation, which were 2h, 8h, and 16h, respectively. In addition, the RNA sequence of rat class-II transactivator (CIITA) the rat was searched, and the target interference sequence was designed concerning the RNA. Results showed that the carrier nanoparticles were spherical without obvious oxygen vacancies, the distribution was relatively tight and concentrated, and the main particle size was 50-140 nm. As the mass ratio of HGPAE to DNA increased, the mobility speed of the nanocarrier/shRNA plasmid complex decreased due to the decrease in surface charge. When the mass ratio reached 90:1, the mobility of the complex was completely blocked, suggesting that the DNA was completely compounded. The counts of PCNA, CK-19, F-VIII-Ag, VEGFA, VEGFB, and VEGFC in the 3 groups all showed a downward trend with the increase of UW time; the count in group B was lower than that of groups A and C. In the PCNA count statistics, there was no obvious difference between group A and group B at UW8h, but there were differences in contrast to group C (p<0.05). It was concluded that the blood supply of the microcirculation of the PVP was extremely important for the transplanted liver tissue. When the blood vessels around the HBD of the rat were completely ischemic, the HBD epithelial cells became the most important target of damage, and the proliferation and changes of the HBD epithelial cells can be directly observed. In addition, the nanocarrier-mediated genes were applied to discuss postoperative rejection. The expression of class-II MHC-II gene in nanocarrier CIITA-shRNA was inhibited, which interfered with the recipient’s immune recognition of the graft, thereby reducing the intensity of the rejection reaction and relieving the rejection reaction.